2011
DOI: 10.1093/jxb/err222
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium localization in root tips of the aluminium-accumulating plant species buckwheat (Fagopyrum esculentum Moench)

Abstract: Aluminium (Al) uptake and transport in the root tip of buckwheat is not yet completely understood. For localization of Al in root tips, fluorescent dyes and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) were compared. The staining of Al with morin is an appropriate means to study qualitatively the radial distribution along the root tip axis of Al which is complexed by oxalate and citrate in buckwheat roots. The results compare well with the distribution of total Al determined by LA-IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 28 publications
(46 reference statements)
2
17
0
1
Order By: Relevance
“…Lumogallion specificity for Al is higher than that of Morin but Lumogallion also stains gallium, in addition to Al [ 26 ] and other metals, such as Fe [ 27 , 28 ]. Furthermore, both the Lumogallion affinity for Al and fluorescence signal intensity are much lower than those of Morin [ 29 ] limiting its use when the detection of trace amounts of Al in tissues is concerned, e.g. in brain.…”
Section: Resultsmentioning
confidence: 99%
“…Lumogallion specificity for Al is higher than that of Morin but Lumogallion also stains gallium, in addition to Al [ 26 ] and other metals, such as Fe [ 27 , 28 ]. Furthermore, both the Lumogallion affinity for Al and fluorescence signal intensity are much lower than those of Morin [ 29 ] limiting its use when the detection of trace amounts of Al in tissues is concerned, e.g. in brain.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the roots of common buckwheat also take up Al in the form of Al 3+ (Ma & Hiradate, 2000), although a different form (Al-oxalate at a 1 : 1 ratio) was also proposed (Klug & Horst, 2010). Al uptake also seems to occur in the root tips (Klug & Horst, 2010;Klug et al, 2011). Once Al is taken up into the root cells, it is complexed with oxalate at a 1 : 3 ratio, forming a nonphytotoxic form of Al (Ma et al, 1997b.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma membrane can acts as a barrier of Al because ions like polyvalent Al 3+ are insoluble in the lipid bilayers. However, Klug et al (2011) found that up to one half of the total of Al in the root apex was located in the symplasm. When Al crossed the membrane, many potential harmful interactions can occur.…”
Section: Discussionmentioning
confidence: 99%